Endenese Fisheries: Exploratory Findings on Environmental Perceptions, Fish Effort, and Overfishing in Eastern Indonesia - Ramenzoni, Victoria C. (Ethnobiology Letters, 2013)
Fishing fleets in South East Asia have recently experienced unprecedented expansion. Consequently, catches and regional diversity have dramatically decreased throughout the Indian Ocean. Regional governments and conservation organizations blame the local fishermen and their use of damaging fishing practices for the present state of resources. However, many of these institutions endorse a narrow perspective on bioeconomic governance and human action (rational action choice) that compromises the understanding of resource use and exploitation among small-scale fisheries. Over the last few decades, there is a growing recognized tradition that points to the importance of ecological systems of knowledge, uncertainty representation, and traditional skills, in conceptualizing processes of environmental decision-making and the likelihood of introducing successful sustainability practices. In line with this perspective, this article presents preliminary findings regarding resource use decision-making processes among Endenese fishing villages in central Flores Island, Indonesia. Grounded on 22 months of ethnographic, experimental and ecological research (semistructured interviews, participant observation, visual surveys, probability and uncertainty assessments), and exploring local cognitive representations of marine processes, climate, ichthyology and the role of luck, this article discusses the current economic representations of small-scale fishers as avid maximizers. It concludes by emphasizing the need to further explore the role of mental models and beliefs regarding uncertainty in motivating fishing effort to design adequate conservation and governance programs.